Applying crisis standards of care to critically ill patients during the COVID‐19 pandemic: Does race/ethnicity affect triage scoring? - Melanie F. Molina; Rebecca E. Cash; Jossie Carreras‐Tartak; Gia Ciccolo; Jordan Petersen; Keizra Mecklai; Giovanni Rodriguez; Noelle Castilla‐Ojo; Okechi Boms; David Velasquez; Wendy Macias‐Konstantopoulos; Carlos A. Camargo Jr; et al. (Journal of the American College of Emergency Physicians Open)
Abstract Objective Given the variability in crisis standards of care (CSC) guidelines during the COVID‐19 pandemic, we investigated the racial and ethnic differences in prioritization between 3 different CSC triage policies (New York, Massachusetts, USA), as well as a first come, first served (FCFS) approach, using a single patient population. Methods We performed a retrospective cohort study of patients with intensive care unit (ICU) needs at a tertiary hospital on its peak COVID‐19 ICU census day. We used medical record data to calculate a CSC score under 3 criteria: New York, Massachusetts with full comorbidity list (Massachusetts1), and MA with a modified comorbidity list (Massachusetts2). The CSC scores, as well as FCFS, determined which patients were eligible to receive critical care under 2 scarcity scenarios: 50 versus 100 ICU bed capacity. We assessed the association between race/ethnicity and eligibility for critical care with logistic regression. Results Of 211 patients, 139 (66%) were male, 95 (45%) were Hispanic, 23 (11%) were non‐Hispanic Black, and 69 (33%) were non‐Hispanic White. Hispanic patients had the fewest comorbidities. Assuming a 50 ICU bed capacity, Hispanic patients had significantly higher odds of receiving critical care services across all CSC guidelines, except FCFS. However, assuming a 100 ICU bed capacity, Hispanic patients had greater odds of receiving critical care services under only the Massachusetts2 guidelines (odds ratio, 2.05; 95% CI, 1.09 to 3.85). Conclusion Varying CSC guidelines differentially affect racial and ethnic minority groups with regard to risk stratification. The equity implications of CSC guidelines require thorough investigation before CSC guidelines are implemented.